A Survey of Petri Net Tools - Thong, Weng Jie; M. A., Ameedeen (Springer, 2015)
Petri net is a mathematical modeling language that can be used to describe a system graphically. It is a strong language that can be used to represent parallel or concurrent activities in a system. With the ease of a Petri net tool, users can view the overall system graphically and edit It with the editor. A Petri net tool can also be used to analyze the performance of the system, generate code, simulate the system and perform model checking on it. A review on twenty Petri net tools in this paper will give the readers an idea on what is a Petri net tool and the main functions of a Petri net tool. This paper can also serve as an introduction of twenty Petri net tools to the reader. however, to date, there are many Petri net tools available to be downloaded online. This survey paper aims to compare twenty Petri net tools in different aspect. This is important as users will not have to read the reviews of Petri net tools online one by one. Just be having a look at the discussion provided, readers can determined the best recommended Petri net tools to be used based on their operating systems and the types of Petri net tool to be analyzed. The main purpose of this survey paper is to recommend Petri net tools to users based on the operating system and the types of Petri net to be analyzed.